Fa'āliyyatu Ṭarīqah at-Taqlīd Wa At-Taḥfīẓ Fīī Ta'allumi Mādati Tamrīn al-Lughah al-'Arabiyyah Fīīl Ma'had Al-Īmān Ponorogo - Ahmad Hidayatullah Zarkasyi; Ahmad Farhan Rif'an Najib; Alif Cahya Setiyadi; Arya Wira Nugraha; Arsya Shafarul Nawenza (Mantiqu Tayr: Journal of Arabic Language, 2024)
In the era of globalization, mastering Arabic has become increasingly important as an international language used  in  many  religious,  academic,  and  professional  contexts. The background of this study centers around the growing importance of mastering Arabic in the era of globalization. There for, this study aims to enhance students' Arabic language skills at exploring the effectiveness of the mimicry and memorizing method in teaching of tamrin lughoh at the Al Iman boarding school. The problem is the low ability of students in speaking Arabic and lack of interest and motivation during the learning process in the classroom. The method used quantitative quasi-experimental method with pre-test and post-test design on two groups: experimental group and control group. The results showed a significant improvement in learning tamrin lughoh and improving students' language skills after the application of the Mim-Mem method. The mean score of the experimental group increased from 21.45 to 27.35, while the control group only increased from 21.25 to 26.45. This shows that the Mim-Mem method is effective in learning tamrin lughoh and improving students' language skills. Researchers suggest that future research places more emphasis on implementation and focuses on increasing the achievement of the values and ultimate goals of good Arabic language learning.